1991
DOI: 10.1128/jb.173.18.5843-5853.1991
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of two Alcaligenes eutrophus gene loci relevant to the poly(beta-hydroxybutyric acid)-leaky phenotype which exhibit homology to ptsH and ptsI of Escherichia coli

Abstract: From genomic libraries of Alcaligenes eutrophus H16 in XL47 and in pVK100, we cloned DNA fragments which restored the wild-type phenotype to poly(j3-hydroxybutyric acid) (PHB)-leaky mutants derived from strains H16 and JMP222. The nucleotide sequence analysis of a 4.5-kb region of one of these fragments revealed two adjacent open reading frames (ORF) which are relevant for the expression of the PHB-leaky phenotype.The 1,799-bp ORF1 represented a gene which was referred to as phbl. The amino acid sequence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 64 publications
4
61
0
1
Order By: Relevance
“…The signaling pathway might also include NPr and EIIA Ntr , as genome sequencing has revealed the presence of both ptsN and npr in the A. vinelandii rpoN operon (551). Similarly, "leaky" Ralstonia eutropha phbI and phbH mutants show diminished accumulation of poly-␤-hydroxybutyrate (687). A close relationship between phbI and phbH and the ptsP and npr genes of E. coli was established (680), although the PhbI protein of R. eutropha lacks the NifA-like extension typical of other EI Ntr s. Mutants of P. aeruginosa (854) or Legionella pneumophila (333) affected in ptsP do not show an obvious phenotype when grown in rich medium.…”
Section: The Pts Ntrmentioning
confidence: 99%
“…The signaling pathway might also include NPr and EIIA Ntr , as genome sequencing has revealed the presence of both ptsN and npr in the A. vinelandii rpoN operon (551). Similarly, "leaky" Ralstonia eutropha phbI and phbH mutants show diminished accumulation of poly-␤-hydroxybutyrate (687). A close relationship between phbI and phbH and the ptsP and npr genes of E. coli was established (680), although the PhbI protein of R. eutropha lacks the NifA-like extension typical of other EI Ntr s. Mutants of P. aeruginosa (854) or Legionella pneumophila (333) affected in ptsP do not show an obvious phenotype when grown in rich medium.…”
Section: The Pts Ntrmentioning
confidence: 99%
“…Generally, PHA synthesis requires high intracellular ratios of NAD(P)H to NAD(P) ϩ and of acetyl-CoA to free CoA (59). However, other factors, which have not been studied in much detail yet, also have an impact on PHA synthesis (52,53). Pseudomonas oleovorans has been demonstrated to accumulate PHA also under carbon-limited conditions (17,58).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic evidence has indicated that in various bacteria, processes regulated by the PTS include (i) transport of non-PTS carbon sources (35), (ii) the net production of carbon and energy storage sources, such as poly-␤-hydroxybutyrate (64,90) and glycogen (91), (iii) the switch between fermentative and respiratory metabolism (36), (iv) flagellar motility (54), and (v) the control of 54 -dependent transcription of carbon and nitrogen metabolic genes (12,46,63,70,74). Some evidence implicates the PTS in the regulation of cell division (44,63).…”
Section: Introductionmentioning
confidence: 99%